PEMBERDAYAAN DAN PENDAMPINGAN REMAJA MASJID MELALUI PELATIHAN MANAJEMEN DAKWAH, ORGANISASI DAN KEPEMIMPINAN - Dedy Susanto (An-Nida : Jurnal Komunikasi Islam, 2013)
Abstract One of the potential society components that could bring in prosperous life was a teenager. Teens needed to be nurtured and empowered to have the skills and expertise to the prosperity of the mosque in the form of knowledge of the proselytizing, proselytizing management, leadership and emotional intelligence and spiritual. Empowerment and teens mentoring intended to make them be good young generation; namely righteous, faithful, knowledgeable, skilled and noble teenagers. To foster Muslim teenagers it can be done in a variety of approaches, including through mosque youth activities. The Implementation by partners of mosque youth. By providing mosque youth preaching about understanding management, organization and leadership, they are expected to resolve the problems that exist in the community. Keywords: empowerment, training, mosque youth, proselytizing management Salah satu komponen masyarakat yang mempunyai potensi untuk memakmurkan adalah remaja. Remaja perlu dibina dan diberdayakan agar mempunyai keterampilan dan keahlian untuk memakmurkan masjid dalam bentuk pengetahuan tentang dakwah, manajemen dakwah, kepemimpinan maupun kecerdasan emosional dan spiritual. Pemberdayaan dan pendampingan remaja bertujuan agar mereka menjadi generasi muda yang baik; yaitu remaja yang shalih, beriman, berilmu, berketerampilan dan berakhlak mulia. Untuk membina remaja muslim bisa dilakukan dalam berbagai pendekatan, diantaranya melalui aktivitas remaja masjid. Pelaksanaannya dapat dilakukan dengan mitra remaja masjid. Dengan memberikan remaja masjid tentang pemahaman manajemen dakwah, organisasi dan kepemimpinan, mereka diharapkan mampu menyelesaikan masalah-masalah yang ada di masyarakat. Kata Kunci: pemberdayaan, pelatihan, remaja masjid, manajemen dakwah